Muslims and humour : essays on comedy, joking, and mirth in contemporary Islamic contexts - Schweizer, Bernard, 1962-; Molokotos-Liederman, Lina; Amin, Yasmin, 1962- (Bristol University Press, 2022)
In this thought-provoking collection, Muslim and non-Muslim academics take a multi-disciplinary approach to humour in Islam. They draw on examples of comedy practices and styles to scope sociological, cultural, theological and political themes, consider humour's role in fundamentalism, and correct misconceptions about laughter in the religion.